Clinical risk factors for patients with myelodysplastic syndromes undergoing allogeneic hematopoietic stem cell transplantation. Issue 1 (31st December 2022) - Teshigawara-Tanabe, Haruka; Hagihara, Maki; Aoki, Jun; Koyama, Satoshi; Takahashi, Hiroyuki; Nakajima, Yuki; Kunimoto, Hiroyoshi; Tachibana, Takayoshi; Miyazaki, Takuya; Matsumoto, Kenji; Tanaka, Masatsugu; Yamazaki, Etsuko; et al.
ABSTRACT: Objectives : Allogeneic hematopoietic stem cell transplantation (allo-HCT) is the only curative treatment for myelodysplastic syndromes (MDS), although predicting post-transplant outcomes remains inconclusive. This study evaluated patients who underwent allo-HCT for MDS to identify prognostic factors and develop a clinical risk model. Methods : We evaluated 55 patients between June 2000 and March 2015 to identify prognostic factors and develop a model for three-year overall survival (OS) and event-free survival (EFS). Cox regression analysis was performed on four factors: age ≥55 years; Hematopoietic Cell Transplant-Comorbidity Index >2; intermediate or worse cytogenetic status based on revised International Prognostic Scoring System; and unrelated donor status associated with poor OS in the univariate analysis. A clinical risk model was constructed using the sum of the regression coefficients and evaluated using receiver operating characteristic analysis and five-fold cross-validation. Results : Patient median age was 51 (range: 30–67) years. Median follow-up was 45.8 (range: 1.27–193) months; the three-year OS and EFS rates were 61.8% and 56.4%, respectively. The areas under the curves (AUCs) for OS and EFS were 0.738 and 0.778, respectively, and the average AUC for 50 times five-fold cross-validation were 0.711 and 0.723 for three-year OS and EFS, respectively. Conclusion : A four-clinical-risk-factor model that could effectively predict post-transplantation outcomes and help decision-making in MDS treatment was developed.